Canada and High-Skill Emigration to the United States: Way Station or Farm System? - Damas de Matos, Ana; Parent, Daniel (Journal of Labor Economics, 2019)
We show that, on the basis of the initial-screening point system used in Canada, immigrants who subsequently move to the United States are more highly educated than their counterparts from the same source countries in the United States and have much better outcomes. High-skill immigrants who transit through Canada before moving to the United States do so fairly early after arrival, and they represent a substantial share of the population of young, highly educated immigrants in Canada. Thus, Canada is best seen as a transitory destination rather than as a training ground for later emigration to the United States.